Improving the efficiency of material transfer system using Value Stream Mapping (VSM): A case study in the shoe industry - Yuliani Fauziah; Erik Odi Wijaya; Indra Setiawan; Bayu Hari Nugroho (Universitas Sultan Ageng Tirtayasa, 2022)
This research was conducted in one of the shoe industries in Indonesia, which has a problem with material buildup in production material storage. The buildup of material can cause the production material transfer system less efficient. The research aims to identify waste in the production material transfer process using current state value stream mapping (VSM), recommend improvement strategies using future state VSM, and design a more efficient production material transfer system. First, we develop a causal loop diagram because it can map the problem. Then, we identify and fix the problem through value stream mapping for more efficient use of resources. The waste identified in the current state value stream mapping consists of waste of over-processing, waste of motion, and waste of useless transportation. In the future-state VSM, the lead time of the material transfer process is reduced by 840 seconds or 14 minutes, the cycle time of the material transfer process is reduced by 731 seconds or 12 minutes, the area needed is reduced by 43.2-meter square, and the total workforce reduced to two people. A 4-hour material transfer system is recommended as a more efficient production material transfer system.